2013
DOI: 10.1371/journal.pone.0079623
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Visual Vertical and Postural Performance in Healthy Children

Abstract: IntroductionVerticality is essential in our life, especially for postural stability. Subjective vertical as well as postural stability depends on different sensorial information: visual, vestibular and somesthesic. They help to build the spatial referentials and create a central representation of verticality. Children are more visuo-dependant than adults; however, we did not find any study focusing on how children develop their sense of verticality.MethodsWe studied two groups of subjects: 10 children (from 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 29 publications
2
28
1
1
Order By: Relevance
“…The absence of visual reference in the dark condition, or a perturbation of visual reference using optokinetic stimulation, can affect the allocentric reference frame used by the child to obtain a good perception of verticality. More specifically, Gaertner et al (14) showed that the accuracy of verticality at six to eight years old was scarce because children in that study were more dependent on visual information, so that the poor estimation of the SVV may have been caused by imperfect or incomplete integration of visual information. We have suggested that the scarce subjective visual vertical performance we observed in younger children could have been due to immaturity of the cortical and central areas involved.…”
Section: Postural Stability In Children Improved During Growthmentioning
confidence: 83%
See 2 more Smart Citations
“…The absence of visual reference in the dark condition, or a perturbation of visual reference using optokinetic stimulation, can affect the allocentric reference frame used by the child to obtain a good perception of verticality. More specifically, Gaertner et al (14) showed that the accuracy of verticality at six to eight years old was scarce because children in that study were more dependent on visual information, so that the poor estimation of the SVV may have been caused by imperfect or incomplete integration of visual information. We have suggested that the scarce subjective visual vertical performance we observed in younger children could have been due to immaturity of the cortical and central areas involved.…”
Section: Postural Stability In Children Improved During Growthmentioning
confidence: 83%
“…A specially constructed subjective visual vertical (SVV) system was used to assess the visual vertical perception, which looked like an elongated clown, and was made from a phosphorescent tube and fluorescent cardboard (14). The clown was placed two metres away from the child, at eye level, and it could be moved to the left or to the right by the child using a remote control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of sex has been advocated in inter individual differences of the short-term visual memory and visiomotor tasks (8,13). Evaluation of tasks involving visual capacity by the mirror box illusion test (14), mental rotation test (15), judgment of line orientation (16) also provide arguments in favor of sex differences in terms of visuomotor capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Visuomotor tasks implicating the judgment of object or line orientation such as SVV appear to be under the influence of sex hormones (5)(6)(7). Women are reported to perform poorer in these tasks and to be more dependent on their visual context (8). Although many studies suggest that children have also a lower capacity in these tasks, due probably to the immaturity of their central nervous system, the influence of sex at early ages is unclear (8,9).…”
mentioning
confidence: 99%